2012
DOI: 10.3892/or.2012.1988
|View full text |Cite
|
Sign up to set email alerts
|

Changes in expression of human serine protease HtrA1, HtrA2 and HtrA3 genes in benign and malignant thyroid tumors

Abstract: Human HtrA proteins are serine proteases involved in essential physiological processes. HtrA1 and HtrA3 function as tumor suppressors and inhibitors of the TGF-β signaling pathway. HtrA2 regulates mitochondrial homeostasis and plays a pivotal role in the induction of apoptosis. The aim of the study was to determine whether the HtrA proteins are involved in thyroid carcinogenesis. We used the immunoblotting technique to estimate protein levels of HtrA1, HtrA2, long and short variants of HtrA3 (HtrA3-L and HtrA3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Zurawa-Janicka et al ( 49 ) assessed HtrA1 in tissue extracts from 40 subjects; 20 with normal thyroid and 20 with follicular (n=12) or papillary (n=8) tumors using WB. Protein band intensities assessed by densitometry yielded relative values.…”
Section: Resultsmentioning
confidence: 99%
“…Zurawa-Janicka et al ( 49 ) assessed HtrA1 in tissue extracts from 40 subjects; 20 with normal thyroid and 20 with follicular (n=12) or papillary (n=8) tumors using WB. Protein band intensities assessed by densitometry yielded relative values.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the PDZ domain is not required for proteolysis and in this respect HtrA3 resembles HtrA1 [109]. Interestingly, proteolysis of a peptide substrate by purified HtrA3 showed typical Michaelis-Menten kinetics [133], suggesting a lack of the intersubunit cooperation typical for allosteric enzymes, including human HtrA2 [76]. However, existence of an unknown so far allosteric regulator of HtrA3 can not be excluded.…”
Section: Htra3 E a Unique Combination Of Features Among Human Htra Prmentioning
confidence: 90%
“…[4]). Moreover, in ovarian and thyroid cancers the HtrA3L and HtrA3S variants were expressed differentially [22,76]. Thus, the HtrA3 expression depends on cancer type.…”
Section: Human Htra Proteins In Cellular Physiology and Pathogenesismentioning
confidence: 90%
“…Subsequent studies have also reported that HTRA1 expression is decreased in different types of cancers, including metastatic cancers. [47][48][49][50][51][52] An early study on ovarian cancer has suggested a high frequency of loss of heterozygosity near HTRA1 may be associated with its decreased 54 Inhibitory effects of HTRA1 on Wnt signalling is protease-independent and may be associated with TGF-β signalling. 54 Down-regulation of HTRA1 in endometrial cancer has shown increased invasive and metastatic ability in tumour cells.…”
Section: The Role Of Htr A1 In C An Cer Smentioning
confidence: 99%